Environmental and economic investigation of telecom site back-up power systems - Erström, Caroline (My University, 2010)
Diesel generators and lead-acid batteries are currently used as telecom site back-up power in areas where the local electricity grid is not always available. Fuel cell systems are an interesting alternative. In this study, environmental and economic aspects of the following five power back-up systems have been investigated: a diesel generator system, a lead-acid battery system, a fuel cell system with H2 from steel bottles (produced from central electrolysis), a fuel cell system with on-site electrolysis, and a fuel cell system with on-site reforming of methanol. Calculations have been performed for different combinations of power demands (1.5 kW, 3 kW, 5 kW, 8 kW) and electricity grid availabilities (99.9%, 99%, 95%, 90%, 75%). The fuel/electricity use is an important factor in the environmental investigation. Based on the four chosen impact categories (abiotic depletion potential, acidification potential, eutrophication potential, and global warming potential), the battery system and the fuel cell system with a reformer have lower potential environmental impact than the diesel system. The two fuel cell systems with H2 from electrolysis could have better environmental performance than the diesel system if the electricity is based on a significant share of renewable energy. However, it is important to remember that the choice of weighting factors has a significant impact on the ranking of the different power systems. The battery system is the cheapest for most of the combinations of power demand and grid availability, especially when there is no need for a change of batteries. Fuel cell systems with H2 bottles or reformer can be a cost-competitive option for smaller power demands and grid availabilities down to 95%, if the site conditions are inappropriate for battery systems and if the investment cost for the fuel cells is lowered. It is suggested that calculations should be performed for a variety of site locations, in order to eliminate some of the uncertainties in the estimates and to be able to identify sites were fuel cell systems can be used. A study capturing a bigger variety in battery configurations should also be executed.
Keywords: Energi; Hållbar utveckling; Informations- och kommunikationsteknik; Miljöteknik; Energy; Sustainable Development; Information & Communication Technology; Environmental engineering